CRISPR/Cas9 genome editing of CCR5 combined with C46 HIV-1 fusion inhibitor for cellular resistant to R5 and X4 tropic HIV-1 - Wannisa Khamaikawin; Chonticha Saisawang; Boonrat Tassaneetrithep; Kanit Bhukhai; Phetcharat Phanthong; Suparerk Borwornpinyo; Angsana Phuphuakrat; Ekawat Pasomsub; Sujittra Chaisavaneeyakorn; Usanarat Anurathapan; Nopporn Apiwattanakul; Suradej Hongeng (Scientific Reports, 2024)
Hematopoietic stem-cell (HSC) transplantation using a donor with a homozygous mutation in the HIV co-receptor CCR5 (CCR5Δ32/Δ32) holds great promise as a cure for HIV-1. Previously, there were three patients that had been reported to be completely cured from HIV infection by this approach. However, finding a naturally suitable Human Leukocyte Antigen (HLA)-matched homozygous CCR5Δ32 donor is very difficult. The prevalence of this allele is only 1% in the Caucasian population. Therefore, additional sources of CCR5Δ32/Δ32 HSCs are required. The Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR-associated (Cas) system is one method to mediate CCR5 knockout in HSCs that has been successfully employed as a gene editing tool in clinical trials. Additional anti-HIV-1 strategies are still required for broad-spectrum inhibition of HIV-1 replication. Here in this study, we combined an additional anti-HIV-1 therapy, which is C46, a cell membrane-anchored HIV-1 fusion inhibitor with the CRISPR/Cas9 mediated knockout CCR5. The combined HIV-1 therapeutic genes were investigated for the potential prevention of both CCR5 (R5)- and CXCR4 (X4)-tropic HIV-1 infections in the MT4CCR5 cell line. The combinatorial CRISPR/Cas9 therapies were superior compared to single method therapy for achieving the HIV-1 cure strategy and shows potential for future applications.
Keywords: CRISPR and Genetic Engineering; Innovation and Socioeconomic Development; HIV Research and Treatment